Preparation and research progress of AlON transparent ceramics - ZHANG Yiming; WU Haoyang; JIA Baorui; QU Xuanhui; QIN Mingli (Fenmo yejin jishu, 2024)
AlON transparent ceramics have been widely used in many fields due to the excellent optical and mechanical properties. The development of AlON transparent ceramics was introduced in the paper, and the reasons affecting the light transmittance of ceramics were illustrated in terms of reflection, absorption, and scattering. The research status of the powder preparation, sintering aid system, molding technology, and sintering technology for the AlON ceramics were described in detail, the existing technical problems were analyzed, and the optimization directions were proposed.